I.F.T.U. & L.S.I. conference re situation in Spain (list of TUC delegates) - International Federation of Trade Unions ; Labour and Socialist International (1937)
021-0004-001 I.F.T.U. & L.S.I. CONFERENCE re Situation in Spain. London - 10-11 March 1937. List of Delegates appointed by the British Trades Union Congress General Council: Mr. H. Berry Mr. E. Bevin, Mr. J. Brown, Mr. A. Conley, Mr. C. Dukes, Mr. E. Edwards, Mr. H.H. Elvin, Mr. W.J. Farthing, Mr. A.A.H. Findlay, Mr. J. Hallsworth, Miss F. Hancock, Mr. A. Hayday, M.P., Mr. G. Hicks, M.P., + Mr. J. Hindle Mr. M. Hodgson, Mr. W. Holmes, x ? Mr. G.A. Isaacs, Mr. J. Jones, Mr. W. Kean, Mr. W. Lawther, Miss A. Loughlin, + Mr. J. Marchbank, + Mr. A. Shaw, Mr. W. Sherwood Mr. W.R. Spence, Mr. W.J.R. Squance, Mr. W. Stott, Mr. G.W. Thomson, Mr. W.R. Townley, Mr. F. Wolstencroft, + Mr. W. Wood. Sir Walter Citrine (General Secretary). Mr. H.V. Tewson (Assistant Secretary). + Apologies for absence from Conference 10 March, but will atend Conference on 11 March. 292/946/21/4